2020
DOI: 10.1016/j.celrep.2020.108503
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiota Composition Modulates the Magnitude and Quality of Germinal Centers during Plasmodium Infections

Abstract: SUMMARY Gut microbiota composition is associated with human and rodent Plasmodium infections, yet the mechanism by which gut microbiota affects the severity of malaria remains unknown. Humoral immunity is critical in mediating the clearance of Plasmodium blood stage infections, prompting the hypothesis that mice with gut microbiota-dependent decreases in parasite burden exhibit better germinal center (GC) responses. In support of this hypothesis, mice wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 66 publications
4
24
0
Order By: Relevance
“…That is, HCM caused by P. falciparum might be associated with alterations in the gut microbiota. Consistent with this notion, a study revealed a remarkable association between the host microbiota composition and P. falciparum infection (Yooseph et al, 2015;Waide et al, 2020).…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…That is, HCM caused by P. falciparum might be associated with alterations in the gut microbiota. Consistent with this notion, a study revealed a remarkable association between the host microbiota composition and P. falciparum infection (Yooseph et al, 2015;Waide et al, 2020).…”
Section: Discussionmentioning
confidence: 78%
“…Malaria is a severe life-threatening disease with approximately 229 million clinical cases and 409,000 deaths in 2019 (WHO, 2020). Malaria has many economic burdens in addition to its health risks (Waide et al, 2020). Human malaria is caused by infection with four different Plasmodium parasites.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that vancomycin-induced decreases in parasitemia early during infection may be the result of changes in the quantity or quality of the P. yoelii-induced antibodies. In support of this possibility, we have shown that low parasite burden in mice mediated by gut microbiota composition is correlated with increased GC B cell numbers, parasite-specific antibody, better GC structure, and quality antibody response that also provided robust protection against lethal rodent Plasmodium challenge (Waide et al, 2020). Alternatively (Zhuang et al, 2019), the reduction in parasitemia following vancomycin treatment may have occurred through augmentation of other aspects of the host immune response.…”
Section: Discussionmentioning
confidence: 81%
“…(d7Van). Seven days after P. yoelii infection, by which time mice have induced GC responses (Figures 6D and 6E) (Waide et al, 2020), mice were treated with either an anti-CD40L monoclonal antibody (clone MR1) that disrupts GC reactions (Foy et al, 1993;Noelle et al, 1992) or an isotype control antibody (IgG) (Figure 6A). If vancomycin-induced changes in gut bacteria affect P. yoelii parasite burden independent of GC reactions, then disrupting GCs would have minimal effect on parasite burden in the vancomycintreated mice.…”
Section: Signals From Gut Bacteria Dynamically Regulate Germinal Center Reactions and Parasite Burdenmentioning
confidence: 99%
See 1 more Smart Citation